Dihydroartemisinin‐piperaquine versus artesunate‐amodiaquine for treatment of malaria infection in pregnancy in Ghana: an open‐label, randomised, non‐inferiority trial. Issue 8 (3rd July 2017) - Osarfo, Joseph; Tagbor, Harry; Cairns, Matthew; Alifrangis, Michael; Magnussen, Pascal
Abstract: Objective: To determine whether dihydroartemisinin‐piperaquine (DHA‐PPQ) is non‐inferior to artesunate‐amodiaquine (ASAQ) for treating uncomplicated malaria infection in pregnancy. Methods: A total of 417 second/ third trimester pregnant women with confirmed asymptomatic Plasmodium falciparum parasitaemia were randomised to receive DHA‐PPQ or ASAQ over 3 days. Women were followed up on days 1, 2, 3, 7, 14, 28 and 42 after treatment start and at delivery for parasitological, haematological, birth outcomes and at 6‐week post‐partum to ascertain the health status of the babies. Parasitological efficacy (PE) by days 28 and 42 were co‐primary outcomes. Analysis was per‐protocol (PP) and modified intention‐to‐treat (ITT). Non‐inferiority was declared if the two‐sided 95% confidence interval for PE at the endpoints excluded 5% lower efficacy for DHA‐PPQ. Secondary outcomes were assessed for superiority. Results: In PP analysis, PE was 91.6% for DHA‐PPQ and 89.3% for ASAQ by day 28 and 89.0% and 86.5%, respectively, by day 42. DHA‐PPQ was non‐inferior to ASAQ with respect to uncorrected PE [adjusted difference by day 28 (DHA‐PPQ‐ASAQ); 3.5% (95%CI: −1.5, 8.5); and day 42: 3.9% (95%CI: −2.7, 10.4)]. ITT analysis gave similar results. PCR to distinguish recrudescence and reinfection was unsuccessful. DHA‐PPQ recipients had fewer adverse events of vomiting, dizziness, and general weakness compared to ASAQ. Both drugs were well‐tolerated, and there was no excess of adverse birth outcomes. Conclusion: DHA‐PPQ was non‐inferior to ASAQ for treatment of malaria infection during pregnancy. No safety concerns were identified. Our findings contribute to growing evidence that DHA‐PPQ is useful for control of malaria in pregnancy.